Utilization of Video Modelling for Social Skills Enhancement for the Autistic: Perspective of Teachers and Parents - Oduro, Prince; Lawer, Richard Ayertey; Khan, Asma; Terkper, Paulina (Journal of Education and Practice, 2025)
Purpose: This study examined the effectiveness of video modelling as a strategy to enhance social skills in children with autism, with particular attention to the perspectives of teachers and parents in the Ghanaian context. Methodology: Adopting a qualitative single case study design, data were collected through semi-structured interviews with 15 participants, comprising 10 teachers and 5 parents. The data were analyzed thematically to uncover patterns in the participants’ experiences and perceptions. Findings: The findings indicate that video modelling is a valuable tool for enabling children with autism to observe and imitate socially appropriate behaviors, such as sharing, friendliness, and politeness. Teachers also supplemented video modelling with additional materials—including real objects, pictures, and cards—to reinforce learning and support children’s comprehension of social cues. Unique Contributions to Theory and Practice: The study highlights the practical relevance of video modelling as an effective instructional approach for fostering social development in children with autism. It recommends that educational institutions in Ghana adopt video modelling as a core teaching method and provide training for teachers and parents on its effective use. Additionally, it underscores the importance of sustained communication between teachers and parents to maintain consistency in social skills development across home and school environments.